2004
DOI: 10.1002/gcc.20056
|View full text |Cite
|
Sign up to set email alerts
|

Deletion mapping suggests that the 1p22 melanoma susceptibility gene is a tumor suppressor localized to a 9‐mb interval

Abstract: Loss of the short arm of chromosome 1 is frequently observed in many tumor types, including melanoma. We recently localized a third melanoma susceptibility locus to chromosome band 1p22. Critical recombinants in linked families localized the gene to a 15-Mb region between D1S430 and D1S2664. To map the locus more finely we have performed studies to assess allelic loss across the region in a panel of melanomas from 1p22-linked families, sporadic melanomas, and melanoma cell lines. Eighty percent of familial mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…If the LOH occurring in these regions of murine tumors is a model for what is happening in human tumors, it may be anticipated that, similarly, multiple and restricted LOH sites will be uncovered in human tumors within the homologous human chromosome 1p32-36 and 10q23-26 regions. Similar multiple discrete, independent LOH sites have, in fact, been described previously in human tumors (Jakobovitz et al, 1996;Kim et al, 1997;Waber et al, 1997;Wistuba et al, 2000;Walker et al, 2004), including in human breast carcinoma (Kerangueven et al, 1997;Wang et al, 2004) and have been suggested to be the mutational signature of oxidative damages (Turker et al, 1999).…”
Section: Discussionsupporting
confidence: 67%
“…If the LOH occurring in these regions of murine tumors is a model for what is happening in human tumors, it may be anticipated that, similarly, multiple and restricted LOH sites will be uncovered in human tumors within the homologous human chromosome 1p32-36 and 10q23-26 regions. Similar multiple discrete, independent LOH sites have, in fact, been described previously in human tumors (Jakobovitz et al, 1996;Kim et al, 1997;Waber et al, 1997;Wistuba et al, 2000;Walker et al, 2004), including in human breast carcinoma (Kerangueven et al, 1997;Wang et al, 2004) and have been suggested to be the mutational signature of oxidative damages (Turker et al, 1999).…”
Section: Discussionsupporting
confidence: 67%
“…Mutations in TGFB-binding proteins may contribute to disturbances in the regulation of cell differentiation and proliferation, and lead to oncogenic transformation. However, no coding mutations of TGFBR3 could be detected in 1p22-linked melanoma kindreds (Walker et al, 2004). Melanoma cell lines showed significantly less allelic 1p loss compared with fresh tumors, indicating that the TGFBR3 gene may not be involved in cellular alterations necessary for the in vitro propagation of melanoma cells.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, transforming growth factor-b receptor type III (TGFBR3) has been identified as a candidate tumor suppressor in one of three melanoma susceptibility loci at chromosome band 1p22 (Walker et al, 2004). TGFBR3, a TGFB-binding glycoprotein that exists in both a membrane-bound and a soluble form, may serve as a receptor accessory molecule in TGFB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The publicly accessible database miRBase 3 was consulted to identify miRNA located on chromosome 1 in the region predicted to harbor a gene involved in melanoma. The data bases TargetScan 3.1 5 (17, 18) and miRgen 4 (15) were used to identify potential targets for miR-137 regulation in melanoma.…”
Section: Methodsmentioning
confidence: 99%
“…In an attempt to discern regions of the genome that might harbor genes contributing to the development of melanoma, several studies have characterized regions of the genome that are lost or amplified in melanoma cell lines and in families with a high risk for melanoma (2). One such region located on chromosome 1p22 harbors a gene or genes that are responsible for increasing melanoma risk but are not yet identified (3). With the identification of microRNAs (miRNA) as important regulators of gene expression, we hypothesized that a miRNA at 1p22 might be regulating target genes associated with a risk of developing melanoma.…”
Section: Introductionmentioning
confidence: 99%